Dynamics research of unbalanced vibrator with variable static moment - Lyutenko, Vasyl; Rudyk, Rostyslav; Nasulloev, Shahrom (Academic journal Industrial Machine Building Civil Engineering, 2020)
Every year the use of vibrating and vibro-impact equipment becomes more and more common. This machinery is successfully used in the construction of solid foundations for a different building. The main element of these vibrating machines is an unbalanced vibrator. We considered the operation of the unbalanced vibrator in the interaction of mechanical and electromagnetic processes and the result was obtained as a mathematical model of dynamic processes during working the vibrator. The developed mathematical model makes it possible to carry out the analysis of the transients during the operation of the unbalanced vibrator, taking into account the inseparable interaction of the electric machine and the mechanical part of the drive